シラセ ヒョウガ リュウイキ ノ ラジオ エコー タンサ - 前, 晋爾; マエ, シンジ; Mae, Shinji (1986)
P(論文) 東クィーンモードランド雪氷研究計画の一環として白瀬氷河流域でラジオエコー探査を行った。その結果, この流域での氷原および, 基盤岩からのエコー強度の分布が得られた。得られた氷厚と, 既に知られている氷床表面高度分布から基盤岩形態を求めた。白瀬氷河の近くでは, 基盤岩高度は海水面高度と等しいかそれ以下であるが, 内陸に入るに従って高度を増し500から1000mに達する。また, モレーンフィールドとして知られている場所では, 氷床表面直下に山が存在することもわかった。一方, 基盤岩からの反射エコー強度の分布から, 白瀬氷河流域主流部の氷床底部には何らかの形で水が存在すること, すなわち氷温が融点になっていることを示している。この事実は, 氷床の動力学考察からの予測と一致している。 Airborne radio echo sounding was carried out in order to measure the thickness of the ice sheet in the Shirase Glacier drainage basin. From the analysis of the result obtained, the bedrock topography was estimated and it was found that the elevation of the bedrock in the upstream area of the basin was about 500-1000m higher than sea level as predicted by preliminary works. The investigation of the echo strength reflected from the bedrock indicates that the echo in the main part of the ice flow in the basin is stronger than in the edge part. Since the strengthening of echo intensity is caused by the existence of water, the strong echo observed in the main part supports an assumption proposed from the thinning of the ice sheet that the main part of the base of the basin is wet and the ice sheet is sliding on the bedrock. departmental bulletin paper